A hotspot of endemism: Oreophytic Taraxacum species (Compositae, Crepidinae) in the mountains of Bulgaria - Štěpánek, Jan; Kirschner, Jan (Phytotaxa, 2022)
The genus Taraxacum (Compositae, Crepidinae) is rather underexplored in the Balkan Peninsula, in spite of high sectional and species diversities and a considerable proportion of endemism to be expected. We focussed our research on mountain areas of Bulgaria. If occasional occurrence of otherwise lowland groups is disregarded, the following Taraxacum sections were recorded: T. sect. Erythrocarpa (treated in a separate paper), T. sect. Rhodocarpa (= T. sect. Alpestria; fourteen species, twelve newly described), T. sect. Crocea (previously referred to as T. sect. Fontana, with six species, five newly described), T. sect. Obliqua (four species, three newly described), and a new section, T. sect. Bulgarica (18 species, seventeen newly described). A single supramontane to subalpine species with an unknown sectional position, T. erzincanense, is also included. The new section, T. sect. Bulgarica, is characterized by a dwarf growth, very short leaves tightly appressed to the ground, enormously broadly winged petioles, appressed, dark, usually narrowly bordered outer phyllaries, and variously coloured achenes, most often with a conical to subcylindrical cone. The diversity of T. sect. Crocea, T. sect. Obliqua and T. sect. Bulgarica involves a high proportion of local endemism, and, in each section, it is concentrated around local sexual species, T. (Obliqua) pyrenaicum subsp. balcanicum, T. (Crocea) paludosiforme and T. (Bulgarica) bulgaricum. The other representatives of mountain sections are agamospermous and polyploid (triploid to hexaploid). The Taraxacum records published by Doll (1978) are revised; the names T. paludosiforme Doll and T. pseudovernelense Doll are lectotypified. Contrary to the published records, species described from the Alps are absent from Bulgaria; there is a single species of T. sect. Rhodocarpa with its geographical range extending from the Romanian Southern Carpathians to Bulgaria. The high proportion of local endemism is accounted for by the young age of the Bulgarian species.